2022
DOI: 10.3390/app12083960
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Pretreatment for Biological Treatment of Reclaimer Wastewater Containing High Concentration N-methyldiethanolamine

Abstract: A wastewater treatment configuration consisting of advanced oxidation pretreatment and biological wastewater treatment process (BWTP) was investigated to treat a reclaimer wastewater generated in a steel-making industry, which contained high concentration MDEA (N-methyldiethanolamine) of up to 20,548 mg/L and other pollutants such as formate, phenol, and thiocyanate. The Fenton, ozone, and peroxone methods were tested as candidates, and the peroxone method was chosen because it could selectively decompose MDEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…5 Therefore, industrial wastewater must undergo strict degradation treatment before discharge. At present, water pollution treatment methods include biological treatment, 6 physical adsorption, 7,8 chemical oxidation, 9 and photocatalytic degradation. 10,11 Among them, photocatalysis stands out among many methods due to its advantages of low cost, high degradation rate, environmental friendliness, and no formation of secondary pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, industrial wastewater must undergo strict degradation treatment before discharge. At present, water pollution treatment methods include biological treatment, 6 physical adsorption, 7,8 chemical oxidation, 9 and photocatalytic degradation. 10,11 Among them, photocatalysis stands out among many methods due to its advantages of low cost, high degradation rate, environmental friendliness, and no formation of secondary pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…A total of nine papers (seven research papers and two review papers) in various fields of wastewater treatment technology including advanced oxidation, microbial fuel cell, ananmmox, and bioflocculant are presented in this Special Issue. Oh et al [1] reported that high-concentration N-methyldiethanolamine wastewater was successfully treated using a wastewater treatment configuration consisting of advanced oxidation and biological wastewater treatment technology. Kim et al [2] reported that the augmentation of calcium and magnesium contributes to alleviating the salinity stress on anammox granules, and is expected to allow for the application of the anammox process to saline wastewater treatment.…”
mentioning
confidence: 99%